Toward a fluid-dynamic description of an entire heavy-ion collision: from the colliding nuclei to the quark-gluon plasma phase - Kirchner, Andreas; Capellino, Federica; Grossi, Eduardo; Flörchinger, Stefan (Physical review, 2025)
The fluid-dynamical modeling of a nuclear collision at high energy usually starts shortly after the collision. A major source of uncertainty comes from the detailed modeling of the initial state. While the collision itself likely involves far-from-equilibrium dynamics, it is not excluded that a fluid theory of second order can reasonably well describe its soft features. Here we explore this possibility and discuss how the state before the collision can be described in that setup, what are the requirements from relativistic causality to the form of the equations of motion, how much entropy production can result from shear and bulk viscous dissipation during the initial longitudinal dynamics, and how one can thus obtain sensible initial conditions for the subsequent transverse expansion. While we do here only first steps, we outline a larger program. If the latter could be successfully completed, then it could lead to a dynamical description of heavy-ion collisions where the only uncertainty lies in the thermodynamic and transport properties of quantum chromodynamics.
Veröffentlicht: 13. August 2025
Gesehen am 14.01.2026